Laminated polyester film for dry film resist

By adjusting the characteristics of surface A and surface B in the dry film resist laminated polyester film, combined with plasma surface treatment, the problems of uneven shape of the resist and poor high-temperature lamination processability are solved, and excellent sliding properties and high-temperature lamination processability are achieved.

CN119856119APending Publication Date: 2025-04-18TORAY INDUSTRIES INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380064981.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-15
Filing Date
2023-08-08
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, when preparing fine wiring, the shape of the resist is uneven, and pinhole defects are easily generated. The film thermal dimensional change rate is difficult to control during high-temperature lamination processing, resulting in poor lamination processability.

Method used

The laminated polyester film for dry film resist with the skewness of surface A and surface B satisfying Ssk-A>Ssk-B is used. By adjusting the number and skewness of surface A and surface B, and combining plasma surface treatment with atmospheric pressure glow discharge, excellent sliding properties and high-temperature lamination processing adaptability are formed.

Benefits of technology

The resistance characteristics and metal roller sliding properties are optimized, the adaptability of high-temperature lamination processing is improved, and the occurrence of pinhole defects and lamination voids is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005304069010000061
    Figure BDA0005304069010000061
  • Figure BDA0005304069010000171
    Figure BDA0005304069010000171
  • Figure BDA0005304069010000261
    Figure BDA0005304069010000261
Patent Text Reader

Abstract

The present invention addresses the problem of providing a laminated polyester film for a dry film resist, which has excellent resist characteristics, excellent slidability with respect to a metal roll, and excellent high-temperature lamination processing adaptability. [Solution] A laminated polyester film for a dry film resist, which is a film in which the skewness (Ssk) of a surface A and a surface B satisfies Ssk-A > Ssk-B, and which is composed of at least two layers in which the surface A and the surface B satisfy the following (1)-(4). (1) The number of protrusions having a height of 10 nm or more and less than 20 nm from the reference surface on the surface (A) is more than 3000 / mm2 and less than 14000 / mm2. (2) The skewness Ssk-A is 1.0 or more and 4.0 or less. (3) The skewness Ssk-B is-0.1 or more and 1.0 or less. (4) (Ssk-A)-(Ssk-B) is 0.1 or more and 3.0 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminated polyester film for dry film resist having a surface having specific characteristics provided on the surface. Background Art

[0002] Polyester resins are used in a variety of industrial fields because of their good processability. In addition, these polyester resins are processed into film-like products (polyester films) that play an important role in current life such as industrial uses, optical product uses, packaging uses, or magnetic recording tape uses.

[0003] In recent years, miniaturization and high integration have been progressing in electronic information equipment, and with this, the wiring of electronic information equipment has also been miniaturized. In the production of fine wiring of these electronic information equipment, a transparent film is often used as a support and a photocurable resin layer (resist layer) is provided on the surface of the substrate bonded with a thin film of copper, and the shape of the copper wiring is depicted using a photoresist technique together with the film, and a dry film resist construction method is used after the film is peeled off.

[0004] For the next generation of products, it is believed that very fine processing with a wiring width of 2 to 5 μm is required. When the ultraviolet irradiation surface (non-coated surface of the resist) of the support film contains particles, there is a possibility that the shape of the resist becomes uneven due to the scattering of ultraviolet light caused by the particles. In addition, there are cases where the particles contained in the film form coarse aggregates, and foreign matter is accidentally mixed in the film-making process, and sometimes pinholes are generated in the resist due to these coarse objects. Therefore, for the ultraviolet irradiation surface (non-coated surface of the resist) of the support film, in addition to requiring the sliding property to the process metal roller, it is also required to be smoother than before and to be a surface that does not produce / mix coarse objects.

[0005] The conditions of the lamination process in the dry film resist are generally based on the thermal properties of the resist layer and the combination with the copper foil substrate used. In general, a rubber roller heated to 90°C or above is used to pressurize it to make it close, but in recent years, the demand for processing under high temperature conditions up to 120-130°C has increased. Generally speaking, if the polyester film is heated at a temperature above the glass transition temperature, the film shrinks thermally, so there is a difference in the thermal dimensional change rate in the width direction of the resist layer during the lamination process, so that due to the poor adhesion between the copper foil substrate and the resist layer, bubbles are trapped (lamination gaps), resulting in defects in the subsequent photoresist process. Therefore, it is important to control the thermal dimensional change rate of the biaxially oriented polyester film in the process of being heated from 90°C to around 130°C (heating process) to improve the lamination processability.

[0006] Generally speaking, a polyester film is wound into a roll shape after being formed in a manufacturing process. At this time, if the film surface is too smooth, the films are closely attached to each other, so the winding property of the film is deteriorated. Therefore, in order to ensure the winding property of the film, a method is known in which particles are added / included in the film to make the film surface rough to a certain extent (forming protrusions on the film surface) (for example, Patent Documents 1 to 4).

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 2017-200761

[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 2017-193173

[0011] Patent Document 3: Japanese Patent Application Laid-Open No. 2021-59031

[0012] Patent Document 4: Japanese Patent Application Laid-Open No. 2021-109441 Summary of the invention

[0013] Problems to be solved by the invention

[0014] However, in the case of protrusions formed on the film surface by particles as shown in Patent Documents 1 and 2, the problem of uneven resist shape due to ultraviolet light scattering caused by the particles during resist curing may be impaired by adjusting the amount of particles added. In addition, there is also the problem of the generation of agglomerates of particles in the film forming process.

[0015] Patent Document 3 discloses a method of coating and laminating a layer containing particles on the surface of a film. However, the coating layer may cause the coating layer components to fall off during contact with a metal roller, and the coating layer components that have fallen off may affect the formation of a fine wiring resist. In addition, in the method of coating and laminating a layer containing particles, there is a possibility that foreign matter may be mixed in from the outside during the coating and drying process, so that coarse matter may be formed.

[0016] Patent Document 4 discloses a method for forming fine protrusions by a method that does not rely on particles, by performing plasma surface treatment using atmospheric pressure glow discharge on a surface that ensures operability (resist non-coated surface). However, since large-diameter particles are used to ensure operability, there is a problem that they become a factor in scattering ultraviolet light when the resist is cured.

[0017] The present invention aims to provide a laminated polyester film for dry film resist which has excellent resist properties and sliding properties to a metal roll and excellent suitability for high temperature lamination processing.

[0018] Means for solving problems

[0019] In order to combine the anti-corrosion properties with the sliding property to the metal roller and further impart the adaptability to high temperature lamination processing, the present invention adopts the following structure. That is,

[0020] [I] A laminated polyester film for dry film resist, wherein the skewness Ssk of surface A and surface B satisfies Ssk-A>Ssk-B, and the film is composed of at least two layers whose surfaces A and B satisfy the following (1) to (4).

[0021] (1) The number of protrusions on the surface A whose height is 10 nm or more and less than 20 nm from the reference surface exceeds 3000 / mm 2 And less than 14000 pieces / mm 2

[0022] (2) Skewness Ssk-A is 1.0 or more and 4.0 or less

[0023] (3) Skewness Ssk-B is greater than -0.1 and less than 1.0

[0024] (4) (Ssk-A) - (Ssk-B) is 0.1 or more and 3.0 or less

[0025] [II] The laminated polyester film for dry film resist according to [I] is a film in which the skewness Ssk of surface A and surface B satisfies Ssk-A>Ssk-B, and is composed of at least two layers in which surface A and surface B satisfy the following (1) to (4).

[0026] (1) The number of protrusions on the surface A whose height from the reference surface is 10 nm or more and less than 20 nm is 4000 / mm 2 Above and 12000 pieces / mm 2 the following

[0027] (2) Skewness Ssk-A is 1.0 or more and 4.0 or less

[0028] (3) Skewness Ssk-B is greater than -0.1 and less than 1.0

[0029] (4) (Ssk-A) - (Ssk-B) is 0.1 or more and 3.0 or less

[0030] [III] The laminated polyester film for dry film resist according to [I] or [II], wherein the thickness of the P1 layer including the surface A is 0.05 μm or more and 0.4 μm or less.

[0031] [IV] The laminated polyester film for dry film resist according to [I] or [II], wherein the maximum protrusion height from the reference plane of the surface A is 20 nm to 140 nm.

[0032] [V] For the laminated polyester film for dry film resist described in [I] or [II], when the number of coarse particles with a major diameter of 2.0 μm or more when observing an area of ​​30 viewing fields in the thickness direction of 3 μm × 220 μm in the length direction of 290 μm in the width direction from the surface A side through a laser microscope is set to NP1 (pieces), NP1 is less than 20.

[0033] [VI] The laminated polyester film for dry film resist according to [I] or [II], wherein when the film dimensional change rate when the film temperature is increased from 90°C to 130°C is set to ΔL90-130°C (ppm / °C), ΔL90-130°C in at least one direction is greater than -50 and less than 150.

[0034] [VII] The laminated polyester film for dry film resist according to [I] or [II], which has a thickness of 11 μm to 50 μm.

[0035] [VIII] The laminated polyester film for dry film resist according to [I] or [II], wherein a photosensitive resin is applied on the surface B described in [I] above, and the exposed surface is the surface A side.

[0036] Effects of the Invention

[0037] The laminated polyester film for dry film resist of the present invention is excellent in resist properties and sliding property with respect to metal rolls, and has excellent suitability for high temperature lamination processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a conceptual diagram showing the surface A (the surface of the P1 layer) measured by a scanning white interference microscope.

[0039] Figure 2 This is a diagram showing the two-layer structure of the laminated polyester film for dry film resist of the present invention.

[0040] Figure 3 This is a diagram showing the three-layer structure of the laminated polyester film for dry film resist of the present invention.

[0041] Figure 4 This is a diagram showing the structure of a laminated body for dry film resist in which a photosensitive resin is laminated on the surface B of the laminated polyester film for dry film resist of the present invention. DETAILED DESCRIPTION

[0042] Hereinafter, the present invention will be described in detail. It should be noted that, in the present specification, the term "to" indicating a numerical range is used to mean that the numerical values ​​described before and after the term are included as the lower limit and the upper limit unless otherwise specified.

[0043] 〔Polyester resin〕

[0044] The "laminated polyester film" in the present invention refers to a film containing a polyester resin as a main component. The main component here refers to a component contained in an amount exceeding 50% by mass in 100% by mass of all components of the film.

[0045] In addition, the polyester resin in the present invention is obtained by polycondensation of a dicarboxylic acid constituent component and a diol constituent component. It should be noted that in the present specification, the constituent component refers to the smallest unit that can be obtained by hydrolyzing a polyester.

[0046] Examples of the dicarboxylic acid constituent component constituting such a polyester include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, 4,4′-diphenyl dicarboxylic acid, and 4,4′-diphenyl ether dicarboxylic acid, or ester derivatives thereof.

[0047] Examples of the diol constituent components constituting such polyesters include aliphatic diols such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,2-butylene glycol, and 1,3-butylene glycol; alicyclic diols such as cyclohexanedimethanol and spiroglycol; and products obtained by linking a plurality of these diols.

[0048] As the polyester resin that can be used in the present invention, from the viewpoint of mechanical properties and transparency, for example, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene 2,6-naphthalate (PEN), and a part of the dicarboxylic acid component of PET copolymerized with isophthalic acid or naphthalene dicarboxylic acid, and a part of the diol component of PET copolymerized with cyclohexanedimethanol, spiroglycol, or diethylene glycol. Among them, polyethylene terephthalate is particularly preferred.

[0049] The polyester film in the laminated polyester film for dry film resist of the present invention is biaxially oriented, so that the mechanical strength of the film is improved and wrinkles are not easily introduced, and the winding property can be improved. In addition, the surface smoothness can be made uniform in the entire film area by applying uniform tensile stress in the stretching process.

[0050] The so-called biaxial orientation here refers to a pattern showing biaxial orientation in wide-angle X-ray diffraction. The polyester film can generally be obtained by stretching an unstretched thermoplastic resin sheet in the length direction and the width direction of the sheet and then performing a heat treatment to complete the crystal orientation. The detailed film-making conditions are described later.

[0051] One embodiment of the laminated polyester film for dry film resist of the present invention is a laminated polyester film, which is a film in which the skewness Ssk of surface A and surface B satisfies Ssk-A>Ssk-B, and is composed of at least two layers in which surface A and surface B satisfy the following (1) to (4).

[0052] (1) The number of protrusions on the surface A with a height of 10 nm or more and less than 20 nm exceeds 3000 / mm 2 And less than 14000 pieces / mm 2

[0053] (2) Skewness Ssk-A is 1.0 or more and 4.0 or less

[0054] (3) Skewness Ssk-B is greater than -0.1 and less than 1.0

[0055] (4) (Ssk-A) - (Ssk-B) is 0.1 or more and 3.0 or less

[0056] The skewness Ssk of the surface A and the surface B and the number of protrusions of 10 nm or more and less than 20 nm on the surface A were measured and calculated by the method shown below using a scanning white interference microscope (VertScan).

[0057] <Measurement using a scanning white interference microscope (VertScan)>

[0058] A 6 cm × 6 cm sample was taken from a laminated polyester film for dry film resist. For each sample, a scanning white interference microscope (device: "VertScan" (registered trademark) VS1540 manufactured by Hitachi HiTech Science Co., Ltd.) was used. For surface A and surface B in the laminated polyester film, a 50x objective lens was used, and the measurement mode was set to WAVE mode. 90 visual fields were measured with a measurement area of ​​113 μm × 113 μm. The sample was placed on the stage and measured in such a way that the Y axis became the length direction of the sample film (the direction in which the film was wound). It should be noted that in the case of a sample whose length direction is unknown, the Y axis is measured in any 1 direction of the sample film, and then the direction is measured by rotating it by 120 degrees, and then the direction is measured by rotating it by another 120 degrees, and the average of the respective measurement results is set as the characteristic of the sample. The sample film to be measured was sandwiched between two metal frames with rubber gaskets, so that the film in the frames was in a tense state (a state where slack and curl of the sample were eliminated) and the sample surface was measured.

[0059] The obtained microscope image was subjected to image processing under the following conditions using surface analysis software VS-Viewer Version 10.0.3.0 built into the microscope to determine the skewness SsK and the number of protrusions of 10 nm or more and less than 20 nm.

[0060] (Image processing conditions)

[0061] Image processing is performed in the following order.

[0062] Interpolation processing: Full interpolation

[0063] Filtering: Median (3×3 pixels)

[0064] ·Surface correction: 4 times.

[0065] <Skewness Ssk>

[0066] The surfaces A and B of the laminated polyester were measured by a scanning white interference microscope in 90 fields of view. For each measured image subjected to the above-mentioned image processing, the Ssk obtained by outputting the numerical value group obtained by selecting "Height Parameters" in the "ISO Parameters" analysis in the surface analysis software together with the following analysis conditions to the parameter table column was obtained as the skewness, and the average value in 80 fields of view excluding the upper and lower 5 fields of view from the values ​​of each field of view was set as the skewness Ssk of the measured surface. When the surfaces A and B of the laminated polyester film are known, the skewness Ssk of each surface is set as Ssk-A and Ssk-B. When the surfaces A and B are unknown, the values ​​of the skewness Ssk of the two sides of the film are compared, and the side with the larger value is set as the surface A, and the side with the smaller value is set as the surface B.

[0067] (ISO parameter analysis conditions)

[0068] The ISO parameter analysis process was performed under the following conditions.

[0069] S-Filter: Automatic

[0070] Normal probability paper

[0071] Number of divisions: 300

[0072] Upper limit of calculation range: 3.000

[0073] Lower limit of calculation range: -3.000

[0074] Parameters: Select "Height Parameters"

[0075] Output: Select "Parameter List"

[0076] (Parameter table output)

[0077] By selecting "Height Parameters" in the "ISO Parameters" window displayed by the above-mentioned ISO parameter analysis and performing "Add to Parameter Table", "Ssk" displayed in the "ISO Parameters" tab of the "Parameter Table" window is used as the skewness Ssk of the film surface.

[0078] <Number of protrusions larger than 10nm and smaller than 20nm>

[0079] After the microscope image observation and image processing of the surface A were performed as described above, the particle analysis processing was performed under the following conditions using the surface analysis software VS-Viewer Version 10.0.3.0 built into the microscope. The number of protrusions with a height of 10 nm or more and less than 20 nm (particles / mm) was obtained by subtracting the number of particles (particles) detected and displayed on the "Particle Analysis" screen at a height threshold of 10 nm (R50 nm, height threshold setting value: 0.02 μm) from the number of particles (particles) detected and displayed on the "Particle Analysis" screen at a height threshold of 10 nm (R50 nm, height threshold setting value: 0.01 μm), and dividing the result by the measurement area (113 μm×113 μm). 2 The same operation is performed in all 90 measured fields of view, and the average value of the measured values ​​in 80 fields of view excluding the fields of view with 5 measured values ​​from the maximum value and the minimum value is set as the number of protrusions with a height of 10 nm or more and less than 20 nm on the above-mentioned A surface of the sample (number / mm 2 ).

[0080] (Particle analysis conditions)

[0081] The protrusion analysis process was performed under the following conditions.

[0082] Analysis type: sudden analysis

[0083] Image correction: No

[0084] ·deal with

[0085] Height threshold: 0.01μm and 0.02μm

[0086] Particle shaping: No

[0087] Reference height: zero plane (average plane)

[0088] ·Judgment object

[0089] Height / depth: -10000μm≤h≤10000μm

[0090] The longest diameter: -10000μm≤d≤10000μm

[0091] Volume: V ≥ 0.0000 μm 3

[0092] Aspect ratio: r ≥ 0.0000

[0093] Histogram: Number of divisions: 50.

[0094] (Reference height: zero plane (average plane))

[0095] As the "zero plane (average plane)" in the above-mentioned reference height (height 0 nm) setting, the plane of the "average height (Ave)" automatically calculated by the following formula in the measurement image (113 μm×113 μm) obtained by microscope image observation and image processing according to the above-mentioned method is used.

[0096] [Number 1]

[0097]

[0098] lx: the range length in the X direction of each measurement image subjected to the above image processing

[0099] ly: the range length in the Y direction of each measurement image subjected to the above image processing

[0100] h(x, y): The height of each image point (x, y) in the measured image after the above image processing.

[0101] The so-called skewness Ssk generally indicates the objectivity of the distribution of hills and valleys in the surface shape. When Ssk=0, the distribution of hills and valleys is vertically symmetrical. When Ssk>0, there are more hills, and when Ssk<0, there are more valleys.

[0102] In the present invention, the skewness Ssk of surface A and surface B satisfies Ssk-A>Ssk-B, which means that surface A is a surface with more hills than surface B. In this case, surface A is a surface that bears sliding properties, and surface B is a surface that ensures smoothness and is suitable for coating a photocurable resin.

[0103] The number of protrusions having a height of 10 nm or more and less than 20 nm in the present invention means that fine protrusions are densely formed on the surface of the laminated polyester film for dry film resist. By densely forming fine protrusions, even when the skewness Ssk-A of the surface A is set to the range described later, it is possible to suppress adhesion when the film and the metal roller are in contact, thereby ensuring sliding properties.

[0104] The number of protrusions with a height of 10 nm or more and less than 20 nm is 3000 / mm 2In the case of less than 14000 pieces / mm, the adhesion with the metal roller is not sufficiently suppressed, so the sliding property may be reduced. 2 In the above case, the uniformity of the shape of the molded resist may be impaired. The number of protrusions with a height of 10 nm or more and less than 20 nm is preferably 4000 / mm 2 Above and 12000 pieces / mm 2 Below, more preferably 5000 pieces / mm 2 Above and 11000 pieces / mm 2 Below, more preferably 5500 pieces / mm 2 Above and 10000 pieces / mm 2 the following.

[0105] The method of forming fine protrusions on the surface A of the laminated polyester film of the present invention so that the number of protrusions with a height of 10 nm or more and less than 20 nm is within the above range preferably includes fine particles with an average primary particle size of 5 nm or more and 30 nm or less in the P1 layer constituting the film surface, and the average primary particle size is more preferably 10 nm or more and 20 nm or less.

[0106] The microparticles used here can use any one of inorganic particles and organic particles, and can also use more than two kinds of particles. As inorganic particles, for example, calcium carbonate, magnesium carbonate, zinc carbonate, titanium oxide, zinc oxide, cerium oxide, magnesium oxide, barium sulfate, zinc sulfide, calcium phosphate, mica, mica, mica, titanium mica, zeolite, talc, clay, kaolin, lithium fluoride, calcium fluoride, montmorillonite, zirconium oxide, wet silica, dry silica, colloidal silica, etc. can be cited. Organic particles, core-shell organic particles, etc. with acrylic resins, styrene resins, silicone resins, polyimide resins, etc. as constituents can be exemplified. Particularly, aluminum oxide (α aluminum oxide, β aluminum oxide, γ aluminum oxide, δ aluminum oxide) particles can be suitably used.

[0107] The amount of fine particles contained in the P1 layer constituting the surface A is preferably 0.5 mass % or more and less than 2.0 mass % relative to the mass of the P1 layer as a whole, and more preferably 0.7 mass % or more and 1.7 mass % or less. When the amount of fine particles is less than 0.5 mass %, sometimes the number of protrusions with a height of 10 nm or more and less than 20 nm is not sufficiently formed, thereby impairing the sliding property with the film and the metal roller. If the amount of fine particles is 2.0 mass % or more, it is sometimes easy to form agglomerates of fine particles, and the resist has loose shapes and pinhole defects.

[0108] As a method for making the number of protrusions with a height of more than 10 nm and less than 20 nm within the above range in addition to containing fine particles, there can be cited a method of transferring the shape to the surface using a mold such as nanoimprinting, surface treatment using UV irradiation, corona treatment using arc discharge, plasma treatment using glow discharge, and the like.

[0109] The skewness Ssk-A of the surface A of the laminated polyester film for dry film resist of the present invention represents the distribution (number, height, length) of the hills (protrusions) in the surface A. The skewness Ssk-A increases or decreases according to the particle size and content of the particles with the largest particle size among the particles contained in the P1 layer. In the present invention, the skewness Ssk-A is greater than 1.0 and less than 4.0. In the case where the skewness Ssk-A is less than 1.0, there is a possibility of damaging the sliding properties with the film and the metal roller due to the small distribution of the hills on the surface A. In the case where the skewness Ssk-A is greater than 4.0, the ultraviolet light is sometimes scattered by the particles contained in the P1 layer when the resist is cured, and the shape of the resist becomes loose. In addition, in the case of being wound into a roll as a laminate coated with a photosensitive resin, there is a possibility of depressions in the photosensitive resin due to the upward push of the protrusions on the surface A. In addition, when the laminated body coated with a photosensitive resin is wound into a roll and stored, the amount of air trapped inside the roll may increase, and oxygen and water vapor contained in the air may permeate the laminated polyester film for dry film resist and the protective film to deteriorate the photosensitive resin. The skewness Ssk-A of the surface A of the laminated polyester film for dry film resist of the present invention is preferably 1.2 or more and 3.0 or less, and more preferably 1.5 or more and 2.5 or less.

[0110] In order to make the skewness Ssk-A within the above range, the average primary particle size of the particles with the largest average primary particle size among the particles contained in the P1 layer constituting the surface A is preferably 50 nm or more and 250 nm or less, more preferably 100 nm or more and 200 nm or less. If the average primary particle size of the particles with the largest average primary particle size among the particles contained in the P1 layer is less than 50 nm, there is a possibility that the skewness Ssk-A is less than 1.0, which may damage the sliding property with the film and the metal roller. If the average primary particle size of the particles with the largest average primary particle size among the particles contained in the P1 layer is greater than 250 nm, even if the content of the particles with the largest average primary particle size among the particles contained in the P1 layer described later and the thickness of the P1 layer are adjusted, there is a possibility that the skewness Ssk-A is greater than 4.0, which may reduce the shape of the resist and the storage property when it is wound into a roll and stored as a laminate coated with a photosensitive resin.

[0111] The so-called average primary particle size here refers to that obtained under the following conditions. The film cross section is observed at 10,000 times using a transmission electron microscope (TEM). At this time, when particles below 1 cm are confirmed in the photo, the TEM observation magnification is changed to 50,000 times for observation. The slice thickness of the TEM is set to about 100 nm, and 100 fields of view are measured by changing the location. The equivalent circular diameter is obtained for all dispersed particles photographed by the photo, and the equivalent circular diameter is plotted on the horizontal axis. The number distribution of particles is plotted as the number of particles on the vertical axis, and the equivalent circular diameter of its peak value is set as the average primary particle size of the particles. Here, when agglomerated particles are confirmed in the photo observed at 10,000 times, they are not included in the above figure. In the case where there are two or more particles with different particle sizes in the film, the number distribution of the equivalent circular diameter becomes a distribution with more than two peaks. In this case, the equivalent circular diameter of each peak is set as the average primary particle size of each particle.

[0112] Measurement device: Transmission electron microscope (TEM) Hitachi H-7100FA

[0113] Measurement conditions: Acceleration voltage 100 kV

[0114] Measurement magnification: 10,000 times, 50,000 times

[0115] Sample conditioning: Ultra-thin film sectioning method

[0116] Observation surface: TD-ZD cross section (TD: width direction, ZD: thickness direction).

[0117] As the particle used as the particle with the largest average primary particle diameter among the particles contained in the P1 layer, any one of inorganic particles and organic particles can be used. As inorganic particles, for example, calcium carbonate, magnesium carbonate, zinc carbonate, titanium oxide, zinc oxide, cerium oxide, magnesium oxide, barium sulfate, zinc sulfide, calcium phosphate, mica, mica, mica titanium, zeolite, talc, clay, kaolin, lithium fluoride, calcium fluoride, montmorillonite, zirconium oxide, wet silica, dry silica, colloidal silica, etc. can be cited. Organic particles, core-shell organic particles, etc., which are composed of acrylic resins, styrene resins, silicone resins, polyimide resins, etc., can be exemplified.

[0118] In order to have both the characteristics of the resist and the sliding property, the content of the particles with the largest average primary particle size among the particles contained in the P1 layer is preferably 0.003 mass % or more and 0.100 mass % or less relative to the weight of the P1 layer as a whole, more preferably 0.005 mass % or more and 0.030 mass % or less, and further preferably 0.008 mass % or more and 0.020 mass % or less. When the content of the particles with the largest average primary particle size among the particles contained in the P1 layer is less than 0.005 mass %, the mountain portion is not fully formed on the surface, so that the skewness Ssk-A is less than 1.0, and there is a possibility of damaging the sliding property with the film and the metal roller. When the content is more than 0.030 mass %, there is a possibility that the skewness Ssk-A is greater than 4.0, and the particles contained in the P1 layer sometimes scatter the ultraviolet light when the resist is cured, and the shape of the resist becomes loose.

[0119] The laminated polyester film for dry film resist of the present invention requires the skewness Ssk-B of surface B to be greater than -0.1 and less than 1.0. The skewness Ssk-B of greater than -0.1 and less than 1.0 indicates that surface B is extremely smooth or slightly protruded, and as a dry film resist, it can be used as a layer for laminating a photosensitive resin. When the skewness Ssk-B is less than -0.1, there is a possibility that the resist shape will deteriorate due to the increase in valleys. When the skewness Ssk-B is greater than 1.0, there is a possibility that the projections of surface B will be transferred to the photosensitive resin, or the resist shape will loosen. The skewness Ssk-B of surface B is preferably greater than 0 and less than 0.7, and more preferably greater than 0 and less than 0.5.

[0120] As a method for making the skewness Ssk of the surface B of the laminated polyester film for dry film resist fall within the above range, the P2 layer constituting the surface B contains substantially no particles or contains particles within the range of the average primary particle size and content described below.

[0121] As the particles included in the P2 layer, any of inorganic particles and organic particles can be used. As inorganic particles, for example, calcium carbonate, magnesium carbonate, zinc carbonate, titanium oxide, zinc oxide, cerium oxide, magnesium oxide, barium sulfate, zinc sulfide, calcium phosphate, mica, aluminum oxide (α aluminum oxide, β aluminum oxide, γ aluminum oxide, δ aluminum oxide) mica (mica), mica titanium, zeolite, talc, clay, kaolin, lithium fluoride, calcium fluoride, montmorillonite, zirconium oxide, wet silica, dry silica, colloidal silica, etc. can be cited. Organic particles, core-shell organic particles, etc., which are composed of acrylic resins, styrene resins, silicone resins, polyimide resins, etc., can be exemplified.

[0122] The average primary particle size of the particles contained in the P2 layer is preferably 100 nm or less, more preferably 70 nm or less. If the average primary particle size is greater than 100 nm, the skewness Ssk-B is greater than 1.0, and there is a possibility that the unevenness is transferred to the photosensitive resin or the resist shape is loosened.

[0123] The content of particles contained in the P2 layer is preferably 0.7% by mass or less, preferably 0.3% by mass or less relative to the mass of the entire P2 layer. If the content of particles contained in the P2 layer is more than 0.7% by mass, the skewness Ssk-B of the surface B may be greater than 1.0, and when a photosensitive resin is laminated on the surface B, there is a possibility that the concavoconvex is transferred to the photosensitive resin or the resist shape formed is loosened.

[0124] As a method for forming protrusions with a skewness Ssk-B within a range of less than 1.0 in addition to including particles in the P2 layer, there are surface treatments such as transferring the shape to the surface using a mold such as nanoimprinting, corona treatment using UV irradiation, arc discharge, and plasma treatment using glow discharge.

[0125] From the perspective of online film forming adaptability and the number of fine protrusions formed, UV irradiation, corona treatment using arc discharge, and plasma treatment using atmospheric pressure glow discharge are preferred. From the perspective of uniformity of treatment and less damage to the film, plasma treatment using atmospheric pressure glow discharge is more preferred. The atmospheric pressure here refers to the range of 700 torr to 780 torr.

[0126] Atmospheric pressure glow discharge treatment is to introduce the film to be treated between the opposing electrodes and the grounded roller, introduce plasma excitation gas into the device, apply high frequency voltage between the electrodes, so that the gas is excited into plasma and glow discharge is performed between the electrodes. As a result, the film surface is finely polished to form protrusions.

[0127] The so-called plasma excitation gas refers to a gas that can be excited by plasma under the above-mentioned conditions. Examples of the plasma excitation gas include rare gases such as argon, helium, neon, krypton, and xenon, nitrogen, carbon dioxide, oxygen, or chlorofluorocarbons such as tetrafluoromethane, and mixtures thereof. In addition, the plasma excitation gas may be used alone or in combination of two or more in any mixing ratio.

[0128] The frequency of the high frequency voltage in the plasma treatment is preferably in the range of 1 kHz to 100 kHz. In addition, the discharge treatment intensity (E value) obtained by the following method is in the range of 10 to 2000 W·min / m 2 It is preferred to treat in the range of 100 to 500 W·min / m from the viewpoint of protrusion formation, and more preferably 100 to 500 W·min / m 2, more preferably 200 to 400 W·min / m 2 If the intensity of the discharge treatment (E value) is too low, protrusions may not be sufficiently formed, and if the intensity of the discharge treatment (E value) is too high, the film may be damaged or polishing may proceed without forming preferred protrusions.

[0129] <How to calculate the discharge treatment intensity (E value)>

[0130] E=Vp×Ip / (S×Wt)

[0131] E: E value (W·min / m 2 )

[0132] Vp: Applied voltage (V)

[0133] Ip: Applied current (A)

[0134] S: Processing speed (m / min)

[0135] Wt: processing width (m).

[0136] When the laminated polyester film for dry film resist of the present invention is subjected to the above-mentioned surface treatment, the surface temperature of the film during the surface treatment is preferably 150° C. or lower, more preferably 100° C. or lower, and most preferably 50° C. or lower.

[0137] If the surface temperature of the film during surface treatment is 150°C or less, the crystallization of the film is inhibited, the formation of coarse protrusions on the surface is prevented, and polishing can be fully performed. On the other hand, if the surface temperature of the film is too low, polishing is not easy to occur, and sometimes it is difficult to form preferred protrusions, so the surface temperature is preferably 10°C or more, more preferably 15°C or more, and further preferably 25°C or more. In addition, the surface treatment temperature can be adjusted by cooling the surface opposite to the treatment surface with a cooling roller or the like.

[0138] The laminated polyester film for dry film resist of the present invention requires that the skewness Ssk difference between surface A and surface B, (Ssk-A)-(Ssk-B) is greater than 0.1 and less than 3.0. The skewness Ssk difference between surface A and surface B indicates that the shape difference between surface A and surface B is small on the basis of controlling Ssk-A and Ssk-B as described above. When (Ssk-A)-(Ssk-B) is less than 0.1, there is a possibility that the protrusions of surface A are not formed sufficiently, which may impair the sliding properties with the film and the metal roller. When (Ssk-A)-(Ssk-B) is greater than 3.0, due to the large shape difference between surface A and surface B, there is a possibility that when the film is wound after film formation and stored as a roller, the protrusions of surface A are pushed up, thereby transferring the concavoconvex to surface B, and the concavoconvex is also transferred to the photosensitive resin after the photosensitive resin is coated, or the shape of the resist is loosened. The skewness Ssk difference between the surface A and the surface B, (Ssk-A)-(Ssk-B), is preferably 0.3 or more and 2.0 or less, and more preferably 0.5 or more and 1.5 or less.

[0139] In order to make the skewness Ssk difference between surface A and surface B, (Ssk-A)-(Ssk-B) within the above range, the laminated polyester film can be achieved by controlling the surface shapes of surface A and surface B by the above method.

[0140] The laminated polyester film for dry film resist of the present invention preferably comprises a P1 layer containing a surface A, and a P2 layer containing a surface B opposite to the P1 layer, and is composed of two or more layers in which the P1 layer and the P2 layer are arranged on the outermost surface. In addition, the layer structure of the laminated polyester film of the present invention is preferably a structure including a P1 layer / P2 layer, or a P3 layer as an intermediate layer between the P1 layer and the P2 layer. In particular, from the viewpoint of being able to have both optical properties and slip properties by adjusting the amount of particles added to each layer, the P3 layer is preferably a layer that does not substantially contain particles.

[0141] There are no particular limitations on the method for laminating the P1 layer with other resin layers such as the P2 layer and the P3 layer, and examples thereof include the coextrusion method described below, a method in which a raw material of other resin layers is fed into an extruder for melt extrusion during film formation and laminated while being extruded from a die (melt lamination method), and a method in which films after film formation are laminated to each other via an adhesive layer, etc. Among these, the coextrusion method in which protrusion formation using the above-mentioned surface treatment and lamination can be performed simultaneously is preferred.

[0142] In the laminated polyester film for dry film resist of the present invention, when the intrinsic viscosity (IV) of the entire film is IV (dl / g), IV (dl / g) is preferably 0.55 or more and 0.80 or less. By making IV (dl / g) 0.55 or more, the mechanical properties in the stretching film-forming process are improved, and the reduction in the film-forming yield due to film rupture can be suppressed. In addition, by making IV 0.8 or less, extrusion defects in the melt extrusion process can be suppressed.

[0143] The laminated polyester film for dry film resist of the present invention preferably has a thickness of the P1 layer including the surface A of 0.05 μm or more and 0.4 μm or less. If the thickness of the P1 layer is less than 0.05 μm, it is possible that the particles contained therein are easy to detach, or the protrusion formation based on the particles inside the P1 layer becomes insufficient, thereby impairing the sliding property with the film and the metal roller. If the thickness of the P1 layer is greater than 0.4 μm, the total number of particles contained in the P1 layer increases, so there is a possibility that the shape of the resist becomes loose. As the thickness of the P1 layer including the surface A, it is more preferably 0.10 μm or more and 0.35 μm or less, and more preferably 0.15 μm or more and 0.30 μm or less.

[0144] The maximum protrusion height of the laminated polyester film for dry film resist of the present invention from the reference plane (determined by scanning white interference microscope and surface analysis described later) on the surface A is preferably 20 nm or more and 140 nm or less. If the maximum protrusion height is less than 20 nm, it is possible to damage the sliding property with the film and metal roller. If the maximum protrusion height is greater than 140 nm, sometimes the shape of the resist is loosened due to the ultraviolet light scattering caused by the protrusion of the surface A, or when it is wound into a roll for storage as a laminated body coated with a photosensitive resin, the amount of air inserted into the roller becomes more and the oxygen and water vapor contained in the air permeate the laminated polyester film for dry film resist and the protective film to deteriorate the photosensitive resin. The maximum protrusion height of the surface A is more preferably 20 nm or more and 100 nm or less, more preferably 30 nm or more and 90 nm or less, and most preferably 40 nm or more and 80 nm or less.

[0145] The laminated polyester film for dry film resist of the present invention is preferably such that the number of coarse particles with a major diameter of 2.0 μm or more existing in a region 3 μm away from the P1 layer in the film thickness direction observed by an optical microscope is defined as NP1 (number / 8.25 mm 2 ) in the case of NP1 being less than 20. The so-called major axis here refers to the longest major axis dimension of the rectangular parallelepiped circumscribed with the projection image of the coarse matter in the image of the coarse matter obtained when the film is observed vertically from the P1 layer side. The number of coarse matter with a major axis of 2.0 μm or more existing in the region of 3 μm in the film thickness direction NP1 (pieces / 8.25 mm 2) is a value reflecting the number of aggregated particles contained in the P1 layer, or even in the P3 layer as an intermediate layer when the P1 layer thickness is less than 3 μm. By setting NP1 to 10 particles / 8.25 mm 2 The following can also suppress the generation of pinhole defects for the next generation of fine resist wiring (L / S 5 / 5μm). 2 ) is preferably in the range of 10 or less, and more preferably in the range of 8 or less.

[0146] The number of coarse particles NP1 (pieces / 8.25 mm) with a major diameter of 2.0 μm or more existing in a region 3 μm away from the P1 layer in the film thickness direction is set to 2 ) is a preferred range of the method of filtering the polymer melted and extruded by an extruder through a filter. If particles contained in the laminated polyester film, catalyst residues when the polyester resin is polymerized, and extremely small foreign matter mixed from the outside of the film-making process also enter the film, they will become coarse protrusion defects, so it is effective to use a filter with high precision, for example, that can capture 95% or more of foreign matter of 2 μm or more or 5 μm or more. In addition, when a particle master batch is used when the particles are contained in the laminated polyester film of the present invention, it is a more preferred mode to use the same filter when the particle master batch is produced.

[0147] In addition, as a method for adjusting the particle content of the particle masterbatch when the particles are included in the laminated polyester film for the dry film resist of the present invention, it is effective to prepare a high-concentration particle masterbatch in advance, and dilute it with a polyester resin that does not substantially contain particles when forming the film to adjust the particle content. At this time, by adjusting the intrinsic viscosity of the polyester resin that does not contain particles to be higher than the intrinsic viscosity of the particle masterbatch in advance, the number of coarse particles with a long diameter of 2.0 μm or more present in the region of 3 μm in the film thickness direction can be reduced. In addition, when the intrinsic viscosity of the particle masterbatch is higher than the intrinsic viscosity of the polyester resin that does not contain particles, or when they are the same, the dispersibility of the particles decreases and the distance between the particles becomes closer, so there is a tendency that the agglomerates of the particles become larger and the coarse particles with a long diameter of 2.0 μm or more present in the region of 3 μm in the film thickness direction increase.

[0148] When the laminated polyester film for dry film resist of the present invention contains particles, the particle content of the particle masterbatch used is preferably 0.5% by mass or less, and more preferably 0.3% by mass or less, relative to the weight of the particle masterbatch, for the particles having the largest particle size among the particles added to the P1 layer. When the particle content of the particle masterbatch of the particles having the largest particle size among the particles added to the P1 layer exceeds 0.5% by mass, when the particles are added to a polyester resin substantially free of particles and dispersed during film formation, the number of coarse particles having a major diameter of 2.0 μm or more that exist in the region of 3 μm in the film thickness direction may increase due to the aggregation of the particles.

[0149] Regarding the particle content of the particle masterbatch used when the laminated polyester film for dry film resist of the present invention contains particles, the particle content of the fine particles added to the P1 layer is preferably 2.0% by mass or less, and more preferably 1.5% by mass or less relative to the weight of the particle masterbatch. When the particle content of the particle masterbatch of the fine particles added to the P1 layer exceeds 2.0% by mass, when the fine particles are added to the polyester resin substantially free of particles and dispersed during film formation, the number of coarse particles with a major diameter of 2.0 μm or more that exist in the region of 3 μm in the film thickness direction may increase due to the aggregation of the particles.

[0150] The laminated polyester film for dry film resist of the present invention needs to have a ΔL90-130°C (ppm / °C) value of -50 to 150 in at least one of the width direction (TD direction) and the length direction (MD direction) when the film dimensional change rate when the film temperature is raised from 90°C to 130°C is set to ΔL90-130°C (ppm / °C).

[0151] The film dimensional change rate ΔL90-130°C (ppm / °C) when the film temperature is raised from 90°C to 130°C is a value obtained by measuring by the thermomechanical analysis (TMA) described later, and is a value indicating the dimensional change rate of the laminated polyester film for dry film resist of the present invention when heated by the high-temperature lamination roller in the lamination process, and is a value indicating that if the value is positive, it expands, and if the value is negative, it shrinks. By making the above ΔL90-130°C (ppm / °C) not less than -50, the heat shrinkage can be reduced to an appropriate range. Thus, in the present invention, the following phenomenon can be suppressed: in the high-temperature lamination process, the biaxially oriented polyester film is thermally shrunk more than the resist layer in the past, so that sometimes curling occurs on the biaxially oriented polyester film side, the copper foil substrate and the resist layer that are closely bonded are peeled off, and floating occurs between the copper foil substrate and the resist layer. As the lower limit value of ΔL90-130°C (ppm / °C), it is more preferably 0 or more, and further preferably 20 or more. In addition, by making the above-mentioned ΔL90-130°C (ppm / °C) less than 150, thermal expansion can be reduced to an appropriate range. In the high-temperature lamination process, the biaxially oriented polyester film has expanded more than the resist layer in the past, so that the resist layer bonded to the biaxially oriented polyester film is sometimes excessively stretched, resulting in tiny defects in the resist layer, which is the starting point for floating between the copper foil substrate and the resist layer, but this phenomenon can be suppressed in the present invention. As the upper limit value of the above-mentioned ΔL90-130°C (ppm / °C), it is more preferably 85 or less.

[0152] Regarding the method of making the above-mentioned ΔL90-130℃ (ppm / ℃) greater than -50 and less than 150, it can be achieved by performing a heat treatment at a temperature above a certain temperature on the biaxially stretched film during the transverse stretching process described later in the film making, and performing a relaxation treatment in the width direction, and performing a relaxation treatment at a temperature above a certain temperature on the biaxially stretched film.

[0153] Specifically, the laminated polyester film is subjected to heat treatment at a temperature of 221°C to 240°C, and a relaxation treatment is performed at a ratio of 1% to 4% in the width direction at the same temperature as the heat treatment temperature, so that the excess orientation stress remaining in the polyester resin molecular chain in the film biaxially oriented by biaxial stretching is relaxed and the film shrinks slightly in the width direction, thereby improving the thermal dimensional stability while maintaining the planarity. The above-mentioned orientation stress relaxation effect is obtained by making the ratio of the relaxation treatment in the width direction 1% or more, and the quality reduction caused by the introduction of periodic wrinkles called corrugations in the laminated polyester film due to rapid heat shrinkage can be suppressed by making the ratio of the relaxation treatment in the width direction 4% or less. The so-called corrugations here refer to the state in which the film has a corrugated shape with a fluctuation height of more than 5 mm in the width direction, such as the shape of a corrugated board (corrugated board) used as a building material. A further preferred range of the heat treatment temperature is 225°C to 240°C, and most preferably 230°C to 240°C. In addition, as a preferred range of the ratio of the relaxation treatment (relax treatment) in the width direction performed at the heat treatment temperature, the lower limit is more preferably 1.5% or more, and the upper limit is more preferably 2.5% or less.

[0154] In order to make the above ΔL90-130°C (ppm / °C) in a more preferred range in the direction where the above ΔL90-130°C (ppm / °C) satisfies -50 or more and 150 or less, it is preferred that after the above width direction relaxation treatment is performed, a width direction relaxation treatment is performed at a temperature of 90°C or more and 150°C or less corresponding to the lamination processing temperature range at a ratio of 0.5% or more and 3% or less. This is because the polyester resin molecular chains in the film are stabilized at the lamination processing temperature by performing the width direction relaxation treatment at the above temperature.

[0155] Furthermore, as a method of performing relaxation treatment at a temperature of 90°C to 150°C, it is further preferred to perform relaxation treatment in the width direction two or more times in two different temperature regions, and it is most preferred to perform relaxation treatment in the width direction at a temperature of 115°C to 150°C at a ratio of 0.5% to 2.0%, and then perform relaxation treatment in the width direction at a temperature of 90°C to less than 115°C at a ratio of 0.3% to 2.0%. This is because by using the preferred relaxation treatment method, the film dimensional change rate ΔL90-110°C (ppm / °C) when the temperature is increased from 90°C to 110°C and the film dimensional change rate ΔL110-130°C (ppm / °C) when the temperature is increased from 110°C to 130°C, which will be described later, can be increased, and accordingly, the value of the above ΔL90-130°C (ppm / °C) can be increased. As the ratio of the relaxation treatment in the width direction performed at a temperature of 115° C. to 150° C., the lower limit is more preferably 1.0% or more, and the upper limit is more preferably 1.8% or less. In addition, as the preferred ratio of the relaxation treatment in the width direction performed at a temperature of 90° C. to less than 115° C., the lower limit is more preferably 0.5% or more, the upper limit is more preferably 1.5% or less, and further preferably 0.8% or less.

[0156] Furthermore, the total relaxation treatment ratio at each temperature after the heat treatment is preferably 5% or less. By making the total relaxation treatment ratio 5% or less, it is possible to suppress the quality reduction caused by the introduction of periodic wrinkles called moire wrinkles due to heat shrinkage in a state where the laminated polyester film is excessively relaxed. More preferably, the total relaxation treatment ratio is 4.5% or less.

[0157] From the viewpoint of matching the thermal dimensional change rate of the above-mentioned anti-etching layer, when the laminated polyester film for the dry film resist of the present invention is used for high-temperature lamination processing, it is a more preferred method to make the above-mentioned ΔL90-130°C (ppm / °C) be above -50 and below 150 in the width direction (TD direction) of the roll during lamination processing.

[0158] The laminated polyester film for dry film resist of the present invention preferably has a thickness of 11 μm or more and 50 μm or less, and more preferably 12 μm or more and 30 μm or less. By making the thickness 50 μm or less, the optical properties such as light transmittance of the film can be further improved. By making the thickness 11 μm or more, the planarity can be further improved when the film is subjected to heat in the process of using the film for various purposes.

[0159] Next, the method for producing the laminated polyester film for dry film resist of the present invention will be described.

[0160] As a method for obtaining the polyester resin used in the present invention, a polymerization method based on a conventional method can be adopted. For example, it can be obtained by subjecting a dicarboxylic acid component such as terephthalic acid or its ester-forming derivatives to an ester exchange reaction or an esterification reaction with a diol component such as ethylene glycol or its ester-forming derivatives by a known method, followed by melt polymerization. In addition, as required, the polyester obtained by the melt polymerization reaction can be subjected to a solid phase polymerization reaction at a temperature below the melting point of the polyester.

[0161] The laminated polyester film of the present invention can be obtained by a conventionally known production method, but by making the stretching and heat treatment steps the above-mentioned conditions, the film dimensional change rate when the film temperature is raised from 90°C to 130°C can be the preferred physical property as described above in at least one direction.

[0162] As a method for producing the laminated polyester film in the present invention, for example, a method in which the raw material dried as required is heated and melted in an extruder, extruded from a die onto a cooled casting drum to be processed into a sheet (melt casting method) can be cited. As other methods, for example, a method in which the raw material is dissolved in a solvent, the solution is extruded from a die onto a support such as a casting drum or an endless belt to form a film, and then the solvent is dried and removed from such a film layer to be processed into a sheet (solution casting method) can also be cited.

[0163] In the case of manufacturing a laminated polyester film with more than two layers by a melt casting method, it is suitable to use an extruder for each layer constituting the laminated polyester film, melt the raw materials of each layer, laminate them in a molten state using a merging device arranged between the extruder and the die, and then guide them to the die, extrude them from the die onto a casting drum, and process them into a sheet to obtain a laminated sheet.

[0164] The laminated sheet processed into a sheet shape is cooled and solidified by static electricity on a casting drum whose surface temperature is preferably cooled to 20°C or more and 60°C or less, to produce an unstretched sheet. The temperature of the casting drum is more preferably 25°C or more and 60°C or less, and further preferably 40°C or more and 55°C or less. By making the surface temperature of the casting drum below 20°C, plasma is irradiated, and the protrusions on the surface of the film after biaxial stretching are fully formed. By making the surface temperature of the casting drum below 60°C, the film is prevented from sticking to the casting drum, and it is possible to suppress the difficulty in obtaining an unstretched sheet.

[0165] Next, the above-mentioned unstretched sheet is subjected to surface treatment. As the surface treatment, for example, a method of transferring a shape to a surface using a model as in nanoimprinting, corona treatment using ultraviolet light irradiation, arc discharge, plasma treatment using glow discharge, etc. can be cited. These surface treatments can be performed just after the unstretched sheet is obtained, or after micro-stretching is performed, or after stretching in the longitudinal and / or transverse directions, but in the present invention, the unstretched sheet is preferably subjected to surface treatment. In addition, the surface subjected to surface treatment can be the surface (drum surface) in contact with the casting drum, or it can be any one of the surfaces (non-drum surface) not in contact with the casting drum. At this time, it is preferably controlled in a manner that the surface temperature of the film surface subjected to surface treatment does not become too high.

[0166] Then, biaxial orientation is performed. As the stretching method, for example, a sequential biaxial stretching method or a simultaneous biaxial stretching method can be cited. The sequential biaxial stretching method in which the longitudinal direction is first stretched and then the width direction is stretched is preferably considered from the viewpoint of obtaining the laminated polyester film of the present invention without being stretched and broken.

[0167] Regarding the stretching conditions when the unstretched film is biaxially stretched, in the case where the polyester film of the present invention has polyester as the main component, as the stretching in the longitudinal direction, it is preferred that the unstretched film is guided to a roller group heated to 70°C or more, stretched in the longitudinal direction (longitudinal direction, i.e., the traveling direction of the film), and cooled with a roller group set to a temperature of 20°C or more and 50°C or less. There is no particular restriction on the lower limit of the temperature of the heating roller in the stretching in the longitudinal direction as long as the stretchability of the sheet is not impaired, but it is preferably higher than the glass transition temperature of the polyester resin used. In addition, the preferred range of the stretching ratio in the longitudinal direction is 3.0 times or more and 4.8 times or less. As a more preferred range, it is 3.5 times or more and 4.8 times or less. If the stretching ratio in the longitudinal direction is 3.0 times or more, orientation crystallization proceeds and the film strength can be improved. On the other hand, by setting the stretching ratio to less than 4.8 times, the dimensional change rate ΔL90-130°C (ppm / °C) when the temperature is increased from 90°C to 130°C in the in-plane perpendicular direction (width direction) relative to the length direction can be controlled within the preferred range and the frequent occurrence of film rupture during manufacturing due to excessive orientation and reduced productivity can be suppressed.

[0168] It is preferred that the obtained uniaxially stretched film stretched in the longitudinal direction is guided to a tenter while being held at both ends by clamps, and stretched to a depth of 3 times or more and 5 times or less in a direction perpendicular to the longitudinal direction (width direction) in an atmosphere heated to a temperature of 70°C or more and 160°C or less.

[0169] Then, the stretched film is preferably subjected to heat treatment to stabilize the internal orientation structure. The thermal history temperature to which the film is subjected during the heat treatment can be confirmed by the temperature of a small endothermic peak (sometimes referred to as Tmeta) that appears immediately below the melting point temperature measured by a differential scanning calorimeter (DSC) described later. Generally speaking, Tmeta is a value of about -5°C representing the heat treatment temperature, so the thermal history applied to the film can be inferred from this value. It is further preferred to perform a relaxation treatment (relax treatment) for the purpose of imparting dimensional stability after the heat treatment.

[0170] The temperature of the heat treatment is preferably not less than (melting point - 40) ° C and not more than the melting point of the thermoplastic resin used, and more preferably not less than (melting point - 40) ° C and not more than (melting point - 15) ° C. Specifically, the laminated polyester film is heat treated at a temperature of not less than 221 ° C and not more than 240 ° C, and a relaxation treatment is performed at a temperature of not less than 1% and not more than 4% in the width direction at the same temperature as the heat treatment temperature, so that the excessive orientation stress remaining in the polyester resin molecular chain in the film biaxially oriented by biaxial stretching is relaxed and the film shrinks slightly in the width direction, thereby achieving an improvement in thermal dimensional stability while maintaining planarity. The above-mentioned orientation stress relaxation effect is obtained by setting the relaxation treatment ratio in the width direction to not less than 1%, and the quality reduction caused by the introduction of periodic wrinkles called moire wrinkles in the laminated polyester film due to rapid heat shrinkage can be suppressed. A further preferred range of the heat treatment temperature is 225° C. to 240° C., and most preferably 230° C. to 240° C. In addition, as a preferred range of the ratio of the relaxation treatment in the width direction performed at the heat treatment temperature, the lower limit is more preferably 1.5% or more, and the upper limit is more preferably 2.5% or less.

[0171] The stretching ratio in the longitudinal direction and the width direction is 3 times or more and 4.8 times or less, respectively, but the area ratio (stretching ratio in the longitudinal direction × stretching ratio in the width direction) is preferably 9 times or more and 22 times or less, and more preferably 9 times or more and 20 times or less. By setting the area ratio to 9 times or more, the molecular orientation of the obtained biaxially oriented polyester film can be promoted to improve the durability, and by setting the area ratio to 22 times or less, the occurrence of rupture during stretching can be suppressed.

[0172] When the thermoplastic resin used is a crystalline polyester such as PET or PEN, and the shape of the unstretched film is imparted by the polishing effect of atmospheric pressure glow discharge treatment, the crystalline part remaining by the polishing treatment is subdivided by stretching, and further by heat treatment, crystal growth is carried out with the part as the core, so that the protrusion shape can be made into a preferred shape. By making the temperature of the heat treatment above the melting point -40°C, the crystal growth becomes sufficient. By making the temperature of the heat treatment below the melting point, the melting of the protrusion can be suppressed.

[0173] The form of the dry film resist laminate using the laminated polyester film for dry film resist of the present invention as a support will be described.

[0174] The laminated polyester film for dry film resist of the present invention preferably has a photosensitive resin laminated on the surface B side. In a film where the skewness Ssk of the surface A and the surface B satisfies Ssk-A>Ssk-B, it means that the surface A is a surface for ensuring operability and the surface B is a surface for ensuring smoothness. By laminating the photosensitive resin on the surface B, the transfer of the unevenness caused by the protrusions on the surface of the laminated polyester film to the photosensitive resin can be suppressed, and the loosening of the resist shape formed and the generation of pinhole defects can be suppressed.

[0175] The method of laminating a photosensitive resin on the laminated polyester film for dry film resist of the present invention is not particularly limited, and a method of coating a photosensitive resin composition in which an organic solvent is mixed in a photosensitive resin in a manner of a prescribed concentration and drying the organic solvent can be cited. As the organic solvent, for example, acetone, methyl ethyl ketone, methanol, ethanol, isopropanol, toluene, propylene glycol monoethyl ether, propylene glycol monomethyl ether acetate, ethyl acetate, butyl acetate, etc. can be cited. They can be used alone or in combination of two or more. The coating liquid of the mixture containing the photosensitive resin composition is uniformly applied to one side of the carrier film by a roller coater method, a rod coater method, etc., and is usually dried in an oven at 50 to 130° C. or at successively higher temperatures, so that a photosensitive resin layer can be laminated on the laminated polyester film for dry film resist.

[0176] In the case of laminating a photosensitive resin, the laminated polyester film for dry film resist of the present invention is preferably coated with a photosensitive resin on the surface B ensuring smoothness, and exposed to ultraviolet light from the surface A during dry film resist processing in order to obtain a high-quality resist. When a film having a skewness Ssk of the surface A and the surface B satisfying Ssk-A>Ssk-B is used as a dry film resist support, by exposing to ultraviolet light from the surface with a large skewness, the influence of refraction and scattering of ultraviolet light caused by particles contained in the layer on the resist shape can be suppressed, and a high-quality resist shape can be obtained.

[0177] [Evaluation method of characteristics]

[0178] [A. Measurement using a scanning white interference microscope (VertScan)]

[0179] A 6 cm × 6 cm sample was taken from a laminated polyester film for dry film resist. For each sample, a scanning white interference microscope (device: "VertScan" (registered trademark) VS1540 manufactured by Hitachi HiTech Science Co., Ltd.) was used. For surface A and surface B in the laminated polyester film, a 50x objective lens was used, and the measurement mode was set to WAVE mode. 90 visual fields were measured with a measurement area of ​​113 μm × 113 μm. The sample was placed on the stage and measured in such a way that the Y axis became the length direction of the sample film (the direction in which the film was wound). It should be noted that in the case of a sample whose length direction is unknown, the Y axis is measured in any 1 direction of the sample film, and then the direction is measured by rotating it by 120 degrees, and then the direction is measured by rotating it by another 120 degrees, and the average of the respective measurement results is set as the characteristic of the sample. The sample film to be measured was sandwiched between two metal frames with rubber gaskets, so that the film in the frames was in a tense state (a state where slack and curl of the sample were eliminated) and the sample surface was measured.

[0180] The obtained microscope images were processed under the following conditions using surface analysis software VS-Viewer Version 10.0.3.0 built into the microscope to determine the skewness SsK, the number of protrusions of 10 nm or more and less than 20 nm, and the maximum protrusion height.

[0181] <Image processing conditions>

[0182] Image processing is performed in the following order.

[0183] Interpolation processing: Full interpolation

[0184] Filtering: Median (3×3 pixels)

[0185] ·Surface correction: 4 times.

[0186] (1) Skewness Ssk

[0187] The surfaces A and B of the laminated polyester were measured by a scanning white interference microscope in 90 fields of view. For each measured image subjected to the above-mentioned image processing, the Ssk obtained by outputting the numerical value group obtained by selecting "Height Parameters" in the "ISO Parameters" analysis in the surface analysis software together with the following analysis conditions to the parameter table column was obtained as the skewness, and the average value in 80 fields of view excluding the upper and lower 5 fields of view from the value of each field of view was set as the skewness Ssk of the measured surface. When the surfaces A and B of the laminated polyester film are known, the skewness Ssk of each surface is set as Ssk-A and Ssk-B. When the surfaces A and B are unknown, the values ​​of the skewness Ssk of the two sides of the film are compared, and the surface with the larger value is set as the surface A, and the surface with the smaller value is set as the surface B.

[0188] <ISO parameter analysis conditions>

[0189] The ISO parameter analysis process was performed under the following conditions.

[0190] S-Filter: Automatic

[0191] Normal probability paper

[0192] Number of divisions: 300

[0193] Upper limit of calculation range: 3.000

[0194] Lower limit of calculation range: -3.000

[0195] Parameters: Select "Height Parameters"

[0196] Output: Select "Parameter List"

[0197] <Parameter table output>

[0198] By selecting "Height Parameters" in the "ISO Parameters" window displayed by the above-mentioned ISO parameter analysis and performing "Add to Parameter Table", "Ssk" displayed in the "ISO Parameters" tab of the "Parameter Table" window is used as the skewness Ssk of the film surface.

[0199] (2) Number of protrusions with a height of 10 nm or more and less than 20 nm from the reference surface

[0200] After the microscope image observation and image processing of the surface A were performed as described above, the particle analysis processing was performed under the following conditions using the surface analysis software VS-Viewer Version 10.0.3.0 built into the microscope. The number of protrusions with a height of 10 nm or more and less than 20 nm (particles / mm) was obtained by subtracting the number of particles (particles) detected and displayed on the "Particle Analysis" screen at a height threshold of 10 nm (R50 nm, height threshold setting value: 0.02 μm) from the number of particles (particles) detected and displayed on the "Particle Analysis" screen at a height threshold of 10 nm (R50 nm, height threshold setting value: 0.01 μm), and dividing the result by the measurement area (113 μm×113 μm). 2 The same operation is performed in all 90 measured fields of view, and the average value of the measured values ​​in 80 fields of view excluding the fields of view with 5 measured values ​​from the maximum value and the minimum value is set as the number of protrusions with a height of 10 nm or more and less than 20 nm on the above-mentioned A surface of the sample (number / mm 2 ).

[0201] <Particle analysis conditions>

[0202] The protrusion analysis process was performed under the following conditions.

[0203] Analysis type: sudden analysis

[0204] Image correction: No

[0205] ·deal with

[0206] Height threshold: 0.01μm and 0.02μm

[0207] Particle shaping: No

[0208] Reference height (surface): zero surface (average surface)

[0209] ·Judgment object

[0210] Height / depth: -10000μm≤h≤10000μm

[0211] The longest diameter: -10000μm≤d≤10000μm

[0212] Volume: V ≥ 0.0000 μm 3

[0213] Aspect ratio: r ≥ 0.0000

[0214] Histogram: Number of divisions: 50.

[0215] <Reference height (surface): Zero surface (average surface)>

[0216] As the "zero plane (average plane)" in the above-mentioned reference height (height 0 nm) setting, the plane of the "average height (Ave)" automatically calculated by the following formula in the measurement image (113 μm×113 μm) obtained by microscope image observation and image processing according to the above-mentioned method is used.

[0217] [Number 2]

[0218]

[0219] lx: the range length in the X direction of each measurement image subjected to the above image processing

[0220] ly: the range length in the Y direction of each measurement image subjected to the above image processing

[0221] h(x, y): The height of each image point (x, y) in the measurement image subjected to the above-mentioned image processing.

[0222] (3) Maximum protrusion height from the reference surface

[0223] The surface A of the laminated polyester was measured using a scanning white interference microscope in 90 viewing fields. For each measured image subjected to the above-mentioned image processing, the maximum protrusion height from the reference surface was obtained by outputting the numerical value group obtained by selecting "Height Parameters" together with the following analysis conditions in the "ISO parameter" analysis in the surface analysis software to the parameter table column. The average value of 80 viewing fields excluding 5 measurement values ​​from the maximum value and the minimum value among the measurement values ​​of each viewing field was set as the maximum protrusion height of the surface A.

[0224] <ISO parameter analysis conditions>

[0225] The ISO parameter analysis process was performed under the following conditions.

[0226] S-Filter: Automatic

[0227] Normal probability paper

[0228] Number of divisions: 300

[0229] Upper limit of calculation range: 3.000

[0230] Lower limit of calculation range: -3.000

[0231] Parameters: Select "Height Parameters"

[0232] Output: Select "Parameter List".

[0233] <Parameter table output>

[0234] Select "Height Parameters" in the "ISO Parameters" window displayed by the above ISO parameter analysis and perform "Add to Parameter Table" to use "Sp" displayed in the "ISO Parameters" tab of the "Parameter Table" window as the maximum protrusion height of the film surface A.

[0235] [B.Thickness (μm)]

[0236] The film thickness was measured at five random locations using a direct-reading thickness gauge in accordance with JIS K7130 (1992) A-2 method in a state where 10 films were stacked. The average value was divided by 10 to obtain the film thickness.

[0237] The thickness of each layer of the film was obtained by the following method. A film cross section was cut out in a direction parallel to the film width direction using a microtome. The cross section was observed with a scanning electron microscope at a magnification of 5000 times to obtain the thickness ratio of each layer of the laminate. The thickness of each layer was calculated from the obtained laminate ratio and the above film thickness.

[0238] <Evaluation of contained particles>

[0239] (1) Particle Observation

[0240] Regarding the laminated polyester film for dry film resist, a microtome was used to prepare small pieces cut in a direction perpendicular to the surface, and the cross-sections thereof were observed using the following TEM (transmission electron microscope: H7100FA manufactured by Hitachi, Ltd.) at 10,000 or 50,000 times to obtain cross-sectional photographs containing particles.

[0241] Measurement device: Transmission electron microscope (TEM) Hitachi H-7100FA

[0242] Measurement conditions: Acceleration voltage 100 kV

[0243] Measurement magnification: 10,000 times, 50,000 times

[0244] Sample conditioning: Ultra-thin film sectioning method

[0245] Observation surface: TD-ZD cross section (TD: width direction, ZD: thickness direction).

[0246] (2) Average primary particle size

[0247] The film cross section was observed at 10,000 times using a transmission electron microscope (TEM). At this time, when particles less than 1 cm were confirmed on the photo, the TEM observation magnification was changed to 50,000 times for observation. The slice thickness of the TEM was set to about 100 nm, and 100 fields of view were measured by changing the location. For all the dispersed particles photographed by the photo, the equivalent circular diameter was calculated, the equivalent circular diameter was plotted on the horizontal axis, and the number distribution of particles was plotted as the number of particles on the vertical axis, and the equivalent circular diameter of its peak value was set to the average particle size of the particles. Here, when agglomerated particles were confirmed on the photo observed at 10,000 times, they were not included in the above figure. In the case where there are two or more particles with different particle sizes in the film, the number distribution of the equivalent circular diameter becomes a distribution with more than two peaks. In this case, the equivalent circular diameter of each peak value is set to the number average particle size of each particle.

[0248] (3) Particle concentration

[0249] 1 g of a sample of each of the P1 layer, P2 layer, and P3 layer of the laminated polyester film for dry film resist of the present invention, which was only cut off, was put into 200 ml of 1N-KOH methanol solution and heated under reflux to dissolve the polymer. 200 ml of water was added to the solution after dissolution, and then the liquid was supplied to a centrifuge to settle the particles and remove the supernatant. Water was further added to the particles for washing and centrifugal separation and repeated twice. The particles obtained by this operation were dried, and their mass (g) was measured to calculate the concentration (mass %) of the particles contained in each layer of the laminated polyester film for dry film resist.

[0250] In the case where the particles contain organic particles, a solvent in which the polymer is dissolved but the organic particles are not dissolved is selected, the polymer is dissolved without heating and refluxing, and the particles are centrifuged to calculate the particle content (mass %) of each layer. Whether the contained particles are organic particles or inorganic particles can be confirmed by whether inorganic matter is detected when the particles are observed by generally known methods such as SEM-EDX.

[0251] <Polymer properties>

[0252] (i) Intrinsic viscosity (IV)

[0253] The sample to be measured (polyester resin (raw material) or the polyester film of the present invention) was dissolved in 100 ml of o-chlorophenol (solution concentration C (sample weight / solution volume) = 1.2 g / 100 ml), and the viscosity of the solution at 25°C was measured using an Ostwald viscometer. In addition, the viscosity of the solvent was measured in the same manner. Using the obtained solution viscosity and solvent viscosity, [η] was calculated by the following formula (1), and the obtained value was set as the intrinsic viscosity (IV) of the entire polyester film.

[0254] ηsp / C=[η]+K[η]2·C···(1)

[0255] (Here, ηsp = (solution viscosity / solvent viscosity) - 1, and K is the Huggins constant (set to 0.343).)

[0256] In addition, when the solution in which the measurement sample was dissolved contained insoluble matter such as inorganic particles, the measurement was performed using the following method.

[0257] (1-1) A measurement sample is dissolved in 100 mL of o-chlorophenol to prepare a solution having a concentration higher than 1.2 g / 100 mL. Here, the weight of the measurement sample provided to o-chlorophenol is referred to as the measurement sample weight.

[0258] (1-2) Next, the solution containing the insoluble matter is filtered, and the weight of the insoluble matter and the volume of the filtrate after filtration are measured.

[0259] (1-3) Add o-chlorophenol to the filtrate after filtration and adjust the ratio of (measured sample weight (g) - weight of insoluble matter (g)) / (volume of filtrate after filtration (mL) + volume of o-chlorophenol added (mL)) to 1.2 g / 100 mL.

[0260] (For example, when a concentrated solution with a measurement sample weight of 2.0 g / solution volume of 100 mL is prepared, when the weight of the insoluble matter when the solution is filtered is 0.2 g and the volume of the filtrate after filtration is 99 mL, adjustment is performed by adding 51 mL of o-chlorophenol. ((2.0 g-0.2 g) / (99 mL+51 mL)=1.2 g / 100 mL))

[0261] (1-4) The solution obtained in (1-3) is used to measure the viscosity at 25° C. using an Ostwald viscometer. The obtained solution viscosity and solvent viscosity are used to calculate [η] using the above formula (5), and the obtained value is defined as the intrinsic viscosity (IV).

[0262] [C. Evaluation of the number of coarse particles]

[0263] The laminated polyester film for the dry film resist of the present invention is cut into pieces of 11 mm×0.75 mm (8.25 mm 2), using an optical microscope (ECLIPSE LV100 manufactured by Nikon), with regard to the surface of the membrane P1 layer, after focusing on the membrane surface, the focus was shifted to the inner side of the membrane in the membrane thickness direction, and the area from the membrane surface to 3μm in the membrane thickness direction was observed, and the number of coarse objects with a long diameter of more than 2.0μm in the area 3μm away from the membrane surface in the membrane thickness direction was measured. The so-called long diameter here refers to the longest long axis dimension of the rectangular parallelepiped circumscribed to the projection image of the coarse objects in the image of the coarse objects obtained when the membrane is observed vertically from the above-mentioned P1 layer side. The number of measurements is set to n=3, and their average value is set to the number of coarse objects NP1 (pieces / 8.25mm) possessed by the sample. 2 ).

[0264] [D. Thermal dimensional change rate ΔL (ppm / °C)]

[0265] <Thermomechanical analysis (TMA) measurement>

[0266] The measurement was performed in the following manner using a thermomechanical measuring apparatus TMA / SS6000 (manufactured by Seiko Instruments) and attached analysis software TMA / SS6100 (manufactured by Seiko Instruments).

[0267] The laminated polyester film for dry film resist was cut into strips to be 30 mm in the measuring direction and 4 mm in the direction perpendicular to the measuring direction, and was attached to the apparatus so that the distance between chucks was 20 mm in the measuring direction.

[0268] Then, in a temperature-controlled furnace (tank), with a tension of 29.4 mN applied along the measuring direction of the sample, the temperature in the furnace was heated from 25°C to 180°C at a heating rate of 10°C / min and then maintained for 10 minutes. The thermal dimensional change rate ΔL (ppm / °C) of the laminated polyester film for dry film resist was calculated using the dimensions at each film temperature, i.e., the distance between the chucks.

[0269] The film temperature here refers to the tank temperature (Temp Cel) recorded every 20 seconds when measuring using the attached analysis software TMA / SS6100 (manufactured by Seiko Instruments Co., Ltd.). In addition, the distance between chucks refers to the TMA length (TMA μm) recorded when measuring using the attached analysis software TMA / SS6100 (manufactured by Seiko Instruments Co., Ltd.).

[0270] (ii) Thermal dimensional change rate ΔL90-130°C during the process of heating from 90°C to 130°C

[0271] According to the above item (i), the thermal dimensional change rate ΔL90-130°C in the process of heating from 90°C to 130°C is calculated using the following formula (1) from the film dimensions at film temperatures of 90°C and 130°C. The measurement is performed twice and the average value thereof is defined as the thermal dimensional change rate ΔL90-130°C (ppm / °C) of the laminated polyester film for dry film resist in the process of heating from 90°C to 130°C.

[0272] ΔL90-130°C (ppm / °C) = [(film size at 130°C (μm)) - (film size at 90°C (μm))] / [130°C - 90°C] × 10000···(1)

[0273] The width direction and the length direction of the laminated polyester film for dry film resist were measured to determine ΔL90-130° C. (ppm / ° C.) in the width direction and the length direction.

[0274] When the direction of the film is unclear, after measuring in any direction, measure in directions offset by 45 degrees to confirm whether there is a direction that satisfies the structure of the present application, and set the direction in which ΔL90-130°C (ppm / °C) satisfies -50 or more and 150 or less as the width direction.

[0275] 〔Application characteristics〕

[0276] [A. Evaluation of dry film resist adaptability]

[0277] (1) Resist wiring pattern preparation and pattern observation

[0278] The photoresist evaluation using the projection exposure method was performed by the following methods a. to c.

[0279] a. On the surface (surface B) opposite to the surface A of the laminated polyester film for dry film resist of the present invention, a photosensitive resin layer is coated in a dark room by gravure coating so as to have a coating thickness of 15 μm. As the photosensitive resin layer, a mixture of a copolymer formed of methacrylic acid, methyl methacrylate, ethyl acrylate, and butyl methacrylate as a thermoplastic resin, trimethylolpropane triacrylate and polyethylene glycol (number average molecular weight 600) dimethacrylate as a photosensitive material, benzophenone and dimethylaminobenzophenone as a photopolymerization initiator, hydroquinone as a stabilizer, and methyl violet as a colorant is used.

[0280] b. The obtained laminate consisting of the laminated polyester film for dry film resist of the present invention and the photosensitive resin layer is overlapped in a manner that the photosensitive resin layer is in contact with a 6-inch Si wafer with a single-side mirror polished surface, and laminated using a rubber roller, and a photomask patterned with chromium metal is arranged thereon, and projection exposure is carried out from the photomask (from the A-side of the biaxially oriented polyester film of the present invention) using an ultraviolet (ultraviolet having a peak at a wavelength of 365nm) stepper exposure machine equipped with a projection lens.

[0281] c. After peeling off the polyester film from the photosensitive resin layer, add the photosensitive resin layer to a container containing developer N-A5 and develop for about 1 minute. Then, take it out of the developer and wash it with water for about 1 minute. Use a scanning electron microscope (SEM) to observe the state of L / S (μm) (line and space) = 5 / 5μm30 lines of the resist wiring pattern produced after development at a magnification of about 800 to 3000.

[0282] (2) Evaluation of fine wiring resist shape

[0283] The 30 resist wiring patterns observed in the above item (1) were checked for the number of wiring patterns having a linear shape missing portion of 0.5 μm or more in the long side portion of the wiring pattern upper surface, and the fine wiring resist shape of the film was evaluated as follows.

[0284] A: The number of missing items is less than 3

[0285] B: The number of missing lines is 4 or more and 7 or less.

[0286] C: The number of lines with deletions is 8 or more and 10 or less.

[0287] D: The number of missing lines is 11 or more.

[0288] As for the fine wiring resist shape evaluation, A to C were good, and A was the most excellent.

[0289] (3) Micro wiring pinhole defects

[0290] The 30 resist wiring patterns observed in the above (1) were checked for the number of wiring patterns having linearly missing portions of 0.5 μm or more in the long sides of the wiring pattern upper surfaces, and the film was evaluated for fine wiring pinhole defects as follows.

[0291] A: The number of lines with pinhole defects is 0

[0292] B: The number of lines having pinhole defects is 1 or more and 5 or less.

[0293] C: The number of lines having pinhole defects is 6 or more and 10 or less.

[0294] D: The number of lines having pinhole defects exceeds 10.

[0295] As for the fine wiring pinhole defect evaluation, A to C were good, and A was the most excellent.

[0296] [B. Evaluation of suitability for high temperature lamination]

[0297] <Resist coating and high temperature lamination processing>

[0298] Photoresist evaluation using the projection exposure method was performed by the following methods ab.

[0299] a. A laminated body in which a resist layer is provided on a laminated polyester film for dry film resist is produced by the composition and method described in the above item (1) a.

[0300] b. After the anti-etching layer surface of the obtained dry film anti-etching layer laminated polyester film sample was overlapped in a manner of contact with a metal substrate (copper foil substrate) bonded with a 3μm thick copper foil cut into A4 size, lamination was performed under the following conditions using a laminator equipped with a temperature-controllable rubber pressure roller.

[0301] (Lamination Processing Conditions)

[0302] Lamination conveying speed: 2m / min

[0303] Lamination roller temperature: 100°C

[0304] Lamination pressure: 0.5MPa

[0305] The lamination process suitability at 100° C. was evaluated by visually checking an A4-sized laminated sample of the copper foil substrate and the laminated polyester film sample for dry film resist when the lamination roll temperature was set to 100° C.

[0306] (1) 100°C lamination void evaluation

[0307] For 10 A4-sized laminated samples of the copper foil substrate and the laminated polyester film sample for dry film resist obtained in the above items (1) a. and b., which were laminated at a lamination roller temperature of 100°C, the presence or absence of lamination voids (floating of the lamination layer) were visually confirmed, and the number of samples with the major diameter of the void exceeding 1 mm was evaluated as follows.

[0308] A: Lamination voids occurred in one or less of the 10 laminated samples.

[0309] B: Among the 10 laminated samples, lamination voids occurred in 2 or more and 3 or less sheets.

[0310] C: Among the 10 laminated samples, lamination voids occurred in 4 or more and 6 or less sheets.

[0311] D: Lamination voids occurred in 7 or more sheets among 10 sheets of laminated samples.

[0312] As for the 100°C lamination void evaluation, A to C were good, and A was the most excellent.

[0313] (2) 100℃ lamination wrinkle evaluation

[0314] Ten A4-sized laminated samples of the copper foil substrate and the biaxially oriented polyester sample laminated at a lamination roll temperature of 100° C. used in the above item (1) were visually checked for the presence or absence of wrinkles of 1 cm or more in length generated during lamination and evaluated as follows.

[0315] A: Among 10 laminated samples, laminate wrinkles occurred in one or less sheets.

[0316] B: Laminated wrinkles occurred in 2 or more and 3 or less of the 10 laminated samples.

[0317] C: Laminated wrinkles occurred in 4 or more and 6 or less of the 10 laminated samples.

[0318] D: Laminated wrinkles occurred in 7 or more of the 10 laminated samples.

[0319] As for the evaluation of 100°C lamination wrinkles, A to C were good, and A was the most excellent.

[0320] [D. Evaluation of sliding properties with metal plates]

[0321] The laminated polyester film for the dry film resist of the present invention was humidified at 23°C and 65% RH, and then cut into a rectangle with a width of 65 mm and a length of 120 mm in the film forming line direction as a sample, and measured in an atmosphere of 23°C and 65% RH using a friction tester (manufactured by Toyo Seiki Co., Ltd.).

[0322] On the measuring sample table of the device, the rectangular sample is placed in such a manner that the stretching direction of the device becomes the length direction of the sample and the surface A side becomes the upper surface (not in contact with the sample table), and the periphery of the sample is fixed to the measuring sample table with a tape. The following metal sample plate is bonded to one side of the wire (sled) connected to the load detection U-type pressure gauge of the device, and the mirror surface of the metal sample plate is placed in such a manner that it overlaps with the surface A of the fixed sample. The total load of the metal sample plate and the wire is 200g.

[0323] After placing a weight of 1 kg on it and letting it stand for 20 seconds so that the surface A of the sample and the surface of the metal sample plate are closely attached, the wire attached to the metal sample plate is stretched under the following conditions, and the maximum value of the load (N; Newton) detected at this time is measured. The measurement is performed 7 times, and the average value of the 5 measured values ​​excluding the highest value 1 point and the lowest value 1 point is used as the average value of the sliding property between the sample and the metal sample plate, and it is evaluated as follows. A is the best and D is the worst.

[0324] (Metal test plate)

[0325] Material: Stainless steel (SUS304 mirror finish)

[0326] Surface roughness: Arithmetic mean roughness 0.012μm

[0327] (Measurement conditions)

[0328] Measuring distance: 70mm

[0329] Measuring speed: 100 mm / min

[0330] A: Maximum load is less than 4N

[0331] B: Maximum load is 4N or more and less than 6N

[0332] C: Maximum load is 6N or more and less than 10N

[0333] D: Maximum load is 10N or more.

[0334] [E. Sliding properties between films]

[0335] After the laminated polyester film for dry film resist of the present invention was humidified at 23°C and 65%RH, two rectangular pieces of 75mm in width and 100mm in length were cut out in the film forming line direction as the length, and the samples were measured at 23°C and 65%RH using a sliding coefficient measuring device (type ST-200, manufactured by Technonik). The rectangular sample was placed and fixed on the measuring sample stage of the device in such a way that the stretching direction of the device became the length direction of the sample and the above-mentioned surface side became the upper side. Another rectangular sample was placed on it in such a way that the above-mentioned surface became the upper side and the stretching direction became the length direction, so that the above-mentioned surface was in contact with the opposite side, and the end of the sample was fixed to the U-type pressure gauge for load detection of the device.

[0336] The film was then left to stand, and a "Teflon" (registered trademark) sheet with a sample contact surface of 6.5 cm × 6.5 cm and a weight of 200 g were placed on it to make the samples close to each other. The upper film was stretched under the following conditions and the static friction coefficient at this time was measured. The average value of 5 measurements was set as the static friction coefficient (μs) for the following evaluation. A to C are good, and A is the best.

[0337] (Measurement conditions)

[0338] Measuring distance: 12mm

[0339] Measuring speed: 210 mm / min

[0340] Detection range: within 1000ms after the start of measurement

[0341] A: Static friction coefficient is less than 1.1

[0342] B: Static friction coefficient is 1.1 or more and less than 1.2

[0343] C: Static friction coefficient is 1.2 or more and less than 1.3

[0344] D: The static friction coefficient is 1.3 or more.

[0345] <Example>

[0346] Hereinafter, the present invention will be described with reference to Examples, but the present invention is not necessarily limited to these Examples.

[0347] <Production of PET-1>

[0348] The melt-polymerized PET containing substantially no particles was obtained by polymerizing terephthalic acid and ethylene glycol using antimony trioxide as a catalyst by a conventional method. The obtained melt-polymerized PET had a glass transition temperature of 81°C, a melting point of 255°C, and an intrinsic viscosity of 0.62.

[0349] <Manufacturing of MB-A>

[0350] During the polymerization of PET-1 in the above item, alumina particles (alumina-1) having an average primary particle size of 20 nm dispersed in ethylene glycol were added after being filtered with a filter that captures 95% or more of foreign matter of 5 μm or more with high precision so that the added amount relative to PET was 2% by mass, thereby obtaining a master particle MB-A. The intrinsic viscosity of the obtained master particle MB-A was 0.59.

[0351] <Manufacturing of MB-B>

[0352] During the polymerization of PET-1, silica particles (silica-1) having an average primary particle size of 200 nm dispersed in ethylene glycol were added after being filtered with a filter that captures 95% or more of foreign matter of 5 μm or more with high precision in an amount of 0.2% by mass relative to PET, thereby obtaining a PET-based master particle MB-B. The intrinsic viscosity of the obtained master particle MB-B was 0.59.

[0353] <Manufacturing of MB-C>

[0354] During the polymerization of PET-1, silica particles (silica-2) having an average primary particle size of 60 nm dispersed in ethylene glycol were added after being filtered with a filter that captures 95% or more of foreign matter of 5 μm or more with high precision so that the added amount relative to PET was 1.0% by mass, thereby obtaining a PET-based master particle MB-C. The intrinsic viscosity of the obtained master particle MB-C was 0.59.

[0355] <Manufacturing of MB-D>

[0356] During the polymerization of PET-1, a cross-linked polystyrene particle slurry (cross-linked polystyrene-1) with a particle size of 300 nm dispersed in water at a particle concentration of 20% was added after high-precision filtration using a filter that captures 95% or more of foreign matter of 5 μm or more, so that the added amount relative to PET was 1% by mass, thereby obtaining a PET-based particle masterbatch MB-D. The intrinsic viscosity of the obtained particle masterbatch MB-D was 0.59.

[0357] <Manufacturing of MB-E>

[0358] During the polymerization of PET-1, a cross-linked polystyrene particle slurry (cross-linked polystyrene-2) with a particle size of 140 nm dispersed in water at a particle concentration of 20% was added after high-precision filtration using a filter that captures 95% or more of foreign matter of 5 μm or more, so that the addition amount relative to PET was 0.2% by mass, thereby obtaining a PET-based master particle MB-D. The intrinsic viscosity of the obtained master particle MB-E was 0.59.

[0359] (Example 1)

[0360] After PET-1, masterbatch MB-A (containing alumina), masterbatch MB-B (containing silica-1), and masterbatch MB-C (containing silica-2) were dried under reduced pressure at 180°C for 2.5 hours, the added amounts of PET-1 and the particles contained in each masterbatch were mixed so as to be the amounts of P1 layer to P3 layer as described in Table 1, and the mixture was supplied to three extruders respectively for melt extrusion. After filtering with a filter, the mixture was merged with a feed block in a stacking manner of P1 layer / P3 layer / P2 layer, and then wound on a cooling roll maintained at 42°C by an electrostatic casting method through a T-die, and cooled and solidified to obtain an unstretched film. In the melt extrusion here, a high-precision filter that captures 95% or more of foreign matter of 5μm or more was used for the filter filtration of the P1 layer and the P2 layer, and a high-precision filter that captures 95% or more of foreign matter of 2μm or more was used for the filter filtration of the P3 layer, and melt extrusion was performed.

[0361] The unstretched film was introduced between the opposing electrodes and the grounded roll, and nitrogen was introduced into the device. When the E value reached 220 W·min / m 2 The surface on the P2 layer side (surface B) was subjected to atmospheric pressure glow discharge treatment under the conditions of . In addition, at this time, the grounded roller was cooled so that the film surface temperature of the treated surface became 30°C.

[0362] After the treated unstretched film passed through a static elimination roll set at a roll temperature of 25°C, it was subjected to sequential biaxial stretching under the conditions described in Table 1. First, it was guided to a stretching roll group heated to 60°C to 100°C and stretched to a total of 3.8 times in the longitudinal direction by a stretching operation, then guided to a tenter and stretched to 4.3 times in the width direction, heat treated at 230°C at a fixed length, and relaxed in the width direction as described in Table 1, thereby obtaining a laminated polyester film having a thickness of 16 μm. The composition and properties of the obtained laminated polyester film are shown in Tables 1 and 2.

[0363] As shown in Table 2, the film had good dry film resist suitability, high temperature lamination process suitability, storage suitability, and handling suitability.

[0364] (Examples 2 to 6)

[0365] A laminated polyester film was obtained in the same manner as in Example 1 except that the contents of particles contained in PET-1, masterbatch MB-A (containing alumina), masterbatch MB-B (containing silica-1), and masterbatch MB-D (containing cross-linked polystyrene-1) in the P1 layer were set to the contents described in Table 1, and the contents of particles contained in the masterbatch MB-A (containing alumina) in the P2 layer were set to the contents described in Table 1. The structure and properties of the obtained laminated polyester film are shown in Tables 1 and 2.

[0366] As shown in Table 2, although any of the dry film resist suitability, high temperature lamination process suitability, and handling suitability were equal to or inferior to those of Example 1, the film had no practical problems.

[0367] (Examples 7 and 8)

[0368] The resin composition of the P2 layer was as described in Table 1, and the surface of the P2 layer was not subjected to plasma treatment, and a laminated polyester film was obtained in the same manner as in Example 1. The composition and properties of the obtained laminated polyester film are shown in Tables 1 and 2.

[0369] As shown in Table 2, the handling suitability of the membrane was equal to or inferior to that of Example 1, but there was no problem in practical use.

[0370] (Examples 9 and 10)

[0371] A laminated polyester film was obtained in the same manner as in Example 1 except that the resin composition in the P2 layer was as described in Table 3-1. The composition and properties of the obtained laminated polyester film are shown in Tables 3-1 and 4-1.

[0372] As shown in Table 4-1, although the dry film resist suitability is equal to or inferior to that of Example 1, the film has no practical problems.

[0373] (Examples 11 and 12)

[0374] A laminated polyester film was obtained in the same manner as in Example 1 except that the thickness of each layer of the P1 layer, the P2 layer, and the P3 layer was set to the configuration described in Table 3-1. The configuration and properties of the obtained laminated polyester film are shown in Tables 3-1 and 4-1.

[0375] As shown in Table 4-1, although the dry film resist suitability and handling suitability were equal to or inferior to those of Example 1, the film had no practical problems.

[0376] (Examples 13 and 14)

[0377] As the resin constituting the P1 layer, instead of using the master batch MB-B (containing silica-1), the particles contained in the master batch MB-C (containing silica-2) or the master batch MB-D (containing cross-linked polystyrene-1) were used in the same manner as in Example 1 to obtain a laminated polyester film. The structure and properties of the obtained laminated polyester film are shown in Tables 3-1 and 4-1.

[0378] As shown in Table 4-1, although the dry film resist suitability and handling suitability were equal to or inferior to those of Example 1, the film had no practical problems.

[0379] (Example 15)

[0380] A laminated polyester film was obtained in the same manner as in Example 1 except that the filtration filter used when melt-extruding the resin constituting the P1 layer was changed to the one described in Table 3-2. The structure and properties of the obtained laminated polyester film are shown in Tables 3-2 and 4-2.

[0381] As shown in Table 4-2, although the dry film resist suitability is equal to or inferior to that of Example 1, the film has no practical problems.

[0382] (Examples 16 and 17)

[0383] A laminated polyester film was obtained in the same manner as in Example 1 except that the sequential biaxial stretching conditions of the laminated polyester film were the heat treatment temperature, relaxation temperature, and relaxation ratio described in Table 3-2. The structure and properties of the obtained laminated polyester film are shown in Tables 3-2 and 4-2.

[0384] As shown in Table 4-2, although the suitability for high temperature lamination is inferior to that of Example 1, the film has no practical problems.

[0385] (Examples 18 and 19)

[0386] As the resin constituting the P1 layer, instead of using the master batch MB-B (containing silica-1), the particles contained in the master batch MB-E (containing cross-linked polystyrene-2) were used in the content described in Table 3-2, and a laminated polyester film was obtained in the same manner as in Example 1. The structure and properties of the obtained laminated polyester film are shown in Tables 3-2 and 4-2.

[0387] As shown in Table 4-2, although the dry film resist suitability and handling suitability were equal to or inferior to those of Example 1, the film had no practical problems.

[0388] (Comparative Examples 1 and 2)

[0389] A laminated polyester film was obtained in the same manner as in Example 1 except that the content of particles contained in the masterbatch MB-A (containing alumina) in the P1 layer was changed to the content described in Table 5. The structure and properties of the obtained laminated polyester film are shown in Tables 5 and 6.

[0390] As shown in Table 6, the film was significantly inferior to Example 1 in terms of dry film resist suitability and handling suitability.

[0391] (Comparative Examples 3 and 4)

[0392] A laminated polyester film was obtained in the same manner as in Example 1 except that the content of particles contained in the masterbatch MB-B (containing silica-1) in the P1 layer was changed to the content described in Table 5. The structure and properties of the obtained laminated polyester film are shown in Tables 5 and 6.

[0393] As shown in Table 6, the film was significantly inferior to Example 1 in terms of dry film resist suitability and handling suitability.

[0394] (Comparative Example 5)

[0395] A laminated polyester film was obtained in the same manner as in Example 1 except that the resin composition in the P2 layer was as described in Table 5 and the surface of the P2 layer was not subjected to plasma treatment. The composition and properties of the obtained laminated polyester film are shown in Tables 5 and 6.

[0396] As shown in Table 6, the handling suitability of the film was significantly inferior to that of Example 1.

[0397] (Comparative Example 6)

[0398] A laminated polyester film was obtained in the same manner as in Example 1 except that the resin composition in the P2 layer was as described in Table 5. The composition and properties of the obtained laminated polyester film are shown in Tables 5 and 6.

[0399] As shown in Table 6, the film has significantly poorer dry film resist suitability and handling suitability than Example 1.

[0400] [Table 1]

[0401]

[0402] [Table 2]

[0403]

[0404] [Table 3-1]

[0405]

[0406] [Table 3-2]

[0407]

[0408] [Table 4-1]

[0409]

[0410] [Table 4-2]

[0411]

[0412] [Table 5]

[0413]

[0414] [Table 6]

[0415]

[0416] Explanation of symbols

[0417] 1. Layer with surface A (P1 layer)

[0418] 2. Surface A that satisfies skewness Ssk-A>Ssk-B

[0419] 3. Layer with surface B (P2 layer)

[0420] 4. Surface B that satisfies skewness Ssk-A>Ssk-B

[0421] 5. Two-layer laminated polyester film consisting of P1 layer and P2 layer

[0422] 6. P3 layer stacked between P1 layer and P2 layer

[0423] 7. Three-layer laminated polyester film consisting of P1 layer, P2 layer, and P3 layer

[0424] 8. Photosensitive resin laminated on surface B

[0425] 9. A laminate composed of a laminated polyester film and a photosensitive resin.

Claims

1. A laminated polyester film for dry film resist, wherein the skewness Ssk of surface A and surface B satisfies Ssk-A>Ssk-B, and the film is composed of at least two layers whose surfaces A and B satisfy the following (1) to (4), (1) The number of protrusions on the surface A whose height from the reference plane is 10 nm or more and less than 20 nm exceeds 3000 / mm 2 And less than 14000 pieces / mm 2 , (2) The skewness Ssk-A is greater than or equal to 1.0 and less than or equal to 4.0, (3) The skewness Ssk-B is greater than -0.1 and less than 1.0, (4) (Ssk-A) - (Ssk-B) is 0.1 or more and 3.0 or less.

2. The laminated polyester film for dry film resist according to claim 1, wherein the skewness Ssk of the surface A and the surface B satisfies Ssk-A>Ssk-B, and the laminated polyester film comprises at least two layers whose surfaces A and B satisfy the following (1) to (4), (1) The number of protrusions on the surface A whose height from the reference plane is 10 nm or more and less than 20 nm is 4000 / mm 2 Above and 12000 pieces / mm 2 the following, (2) The skewness Ssk-A is greater than or equal to 1.0 and less than or equal to 4.0, (3) The skewness Ssk-B is greater than -0.1 and less than 1.0, (4) (Ssk-A) - (Ssk-B) is 0.1 or more and 3.0 or less. 3 . The laminated polyester film for a dry film resist according to claim 1 , wherein the thickness of the P1 layer including the surface A is 0.05 μm or more and 0.4 μm or less. 4 . The laminated polyester film for dry film resist according to claim 1 , wherein the maximum protrusion height from the reference plane of the surface A is 20 nm or more and 140 nm or less.

5. The laminated polyester film for dry film resist according to claim 1 or 2, wherein when the number of coarse particles having an equivalent circle major diameter of 2.0 μm or more is defined as NP1 when an area of ​​30 viewing fields of 3 μm in the thickness direction, 220 μm in the length direction, and 290 μm in the width direction is observed from the surface A side through a laser microscope, NP1 is 20 or less, and the unit of NP1 is piece.

6. The laminated polyester film for dry film resist according to claim 1 or 2, wherein when the film dimensional change rate when the film temperature is increased from 90°C to 130°C is defined as ΔL90-130°C, ΔL90-130°C in at least one direction is greater than -50 and less than 150, and the unit of ΔL90-130°C is ppm / °C. 7 . The laminated polyester film for dry film resist according to claim 1 , which has a thickness of 11 μm to 50 μm.

8. The laminated polyester film for dry film resist according to claim 1 or 2, wherein a photosensitive resin is coated on the surface B described in claim 1, and the exposed surface is the surface A.

Citation Information

Patent Citations

  • Polyester film

    JP2021109441A